Analysis of the Impact of Artificial Intelligence on Enterprise Financial Accounting Work - Huang, Xinyu (Transactions on Economics, Business and Management Research, 2024)
With the rapid growth of technology, the field of artificial intelligence (AI) is innovating at an unprecedented speed and deeply affecting various industries, including corporate financial accounting work. In the current financial field, with the increasing trend of intelligent financial accounting, large enterprises have fully realized the intelligence of basic accounting processing and basic analysis. The application of new financial technologies such as financial robots and automation tools not only greatly improves the efficiency and accuracy of accounting work, but also brings new growth opportunities for enterprises. For enterprises, the introduction of AI means that the processing and analysis capabilities of financial data have been greatly improved. Through intelligent algorithms and big data processing, AI can quickly and accurately complete tedious tasks such as voucher entry, classification, and summarization, and automatically identify and solve potential risk problems. This not only frees up manpower, allowing enterprises to invest more energy in strategic decision-making and value creation, but also effectively improves the reliability and security of financial data. This article explores the impact of AI on corporate financial accounting work.